Combination of Tofu and Fermented Taro Leaf Midrib on Growth Maggot Black Soldier Fly (Hermetia illucens) - Hutasoit, Juwita; Christiana, Ivone; Monalisa, Shinta Sylvia; Rosita, Rosita; Yulintine, Yulintine; Maryani, Maryani (Jurnal Akuakultur SEBATIN, 2023)
This study aims to determine the effect of different combinations of tofu and fermented taro leaf midrib on the growth of Maggot Black Soldier Fly. The research method used is the experimental method using a Completely Randomized Design (CRD) which consists of 4 levels of treatment, namely A (100% tofu); B (75% tofu+ 25% fermented taro leaf midrib); C (50% tofu + 50% fermented taro leaf midrib); D (25% tofu + 75% fermented taro leaf midrib). Parameters observed were BSF maggot length and weight growth, digested feed conversion efficiency (ECD), waste reduction index (WRI), BSF maggot productivity. Analysis of the data used was Analysis of Variance (ANOVA) and to determine the best treatment using a follow-up test in the form of Duncan's test with a significance level of 5%. The results showed that different combinations of tofu and fermented taro leaf midrib had a significant effect on the growth of Maggot BSF. The best combination of tofu and fermented taro leaf midrib on the growth of Maggot BSF was the use of 75% tofu + 25% fermented taro leaf midrib which has a significant effect when compared to other treatments